2022
DOI: 10.3390/genes13112116
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Chloroplast Genome of Cardamine hupingshanensis and Phylogenetic Study of Cardamine

Abstract: Cardamine hupingshanensis (K. M. Liu, L. B. Chen, H. F. Bai and L. H. Liu) is a perennial herbal species endemic to China with narrow distribution. It is known as an important plant for investigating the metabolism of selenium in plants because of its ability to accumulate selenium. However, the phylogenetic position of this particular species in Cardamine remains unclear. In this study, we reported the chloroplast genome (cp genome) for the species C. hupingshanensis and analyzed its position within Cardamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…However, earlier phylogenetic studies on Cardamine indicated a close connection between clade II and clade I, as Raman and Park ( 2021 ) and Huang et al. ( 2022 ) reported. To elucidate the interrelationship among the three clades, it appears imperative to procure more samples and do further investigation.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…However, earlier phylogenetic studies on Cardamine indicated a close connection between clade II and clade I, as Raman and Park ( 2021 ) and Huang et al. ( 2022 ) reported. To elucidate the interrelationship among the three clades, it appears imperative to procure more samples and do further investigation.…”
Section: Resultsmentioning
confidence: 86%
“… 2020 ), Cardamine hupingshanensis (NC_065146) (Huang et al. 2022 ), Cardamine impatiens (NC_026445) (Hu et al. 2015 ), Cardamine kitaibelii (NC_049610) (Walden et al.…”
Section: Resultsmentioning
confidence: 99%
“…Simple sequence repeats are widely served as molecular markers for population genetic analyses, polymorphism identification, and taxonomic analyses [68]. Here, we identified the SSRs in the ten Rorippa species, ranging from 102 to 111, which is comparable to other Brassicaceae in numbers [69,70]. The number of poly (G)/(C) SSRs in the Rorippa plastome is significantly less than that of poly (A)/(T), which agrees with the results of other taxa [71].…”
Section: Plastome Evolution Of Rorippamentioning
confidence: 88%
“…Genome sequence analysis indicates that the divergence between C. hirsuta and Arabidopsis thaliana occurred around 32 Mya, and that C. hirsuta and C. hupingensis diverged about 6.5 Mya. Phylogenetic analyses based on 79 protein coding genes in the chloroplast genome revealed that 17 Cardamine species formed three different clades and C. hupingshanensis is more closely related to C. circaeoides (Huang et al 2022).…”
Section: Introductionmentioning
confidence: 99%